Gut microbiota and gut-derived metabolites are altered and associated with dietary intake in women with polycystic ovary syndrome - Thaís Rasia da Silva; Lucas Bandeira Marchesan; Pabulo Henrique Rampelotto; Larisse Longo; Tiago Franco de Oliveira; Rikard Landberg; Vanessa de Mello; Poli Mara Spritzer (Journal of Ovarian Research)
Abstract Background Disturbances in the gut microbiota may act as mechanisms influencing the interplay between dietary factors and metabolic disorders. Studies have demonstrated that these alterations are associated with the diagnosis of polycystic ovary syndrome (PCOS). Within this context, we aimed to investigate associations between gut microbiota, gut-derived metabolites (short-chain fatty acids [SCFAs] and indole-3-propionic acid [IPA]), and dietary intake in women with PCOS. Methods We conducted a cross-sectional study of 24 women with PCOS, previously recruited for two studies at our research center, compared with 14 age-matched healthy controls. The mean (SD) age of all 38 participants was 33.3 (7.5) years, and the mean (SD) body mass index was 29.5 (4.8) kg/m2. Primary outcomes included gut microbiota analysis by sequencing the V4 region of the 16 S rRNA gene, serum IPA levels measured by liquid chromatography/triple-quadrupole mass spectrometry (LC-QqQ-MS), and fecal and plasma SCFA levels measured by LC-MS/MS. Results Gut microbiota diversity, composition, and metabolic pathways differed between the PCOS and control groups. A higher abundance of two operational taxonomic units specializing in complex carbohydrate metabolism was observed in healthy control women. The PCOS group exhibited a less favorable dietary intake than the control group, and a significant correlation was observed between gut microbiota composition and dietary glycemic load in PCOS (r = 0.314, P = 0.03 in Mantel test). Multivariable-adjusted linear regression models indicated that lower levels of IPA and higher circulating levels of two SCFAs (acetic acid and propionic acid) were independently associated with the diagnosis of PCOS. Conclusions Our data support the differentiation between women with PCOS and healthy controls based on gut microbiota analysis. Furthermore, changes in gut bacteria and their metabolites could be, at least in part, the biological mechanism by which a low glycemic load diet may potentially improve PCOS-related reproductive and cardiometabolic outcomes.